Fatty acid compositions of fish oil extracted from different parts of Indian mackerel (Rastrelliger kanagurta) using various techniques of supercritical CO2 extraction. - F., Sahena; Sarker, Zaidul Islam; Selamat, Jinap; Abdul Manap, Mohd Yazid; Khatib, Alfi; N.A.N., Norulaini (Elsevier, 2010)
Fatty acid compositions of fish oil extracted from different parts of Indian mackerel (Rastrelliger kanagurta) using various techniques of supercritical carbon dioxide (SC-CO2) at optimised conditions (35 MPa, 60 °C, 2 ml/min) were analysed and compared to the results of Soxhlet extraction. The amount of polyunsaturated fatty acids (PUFA) recovered (as a percentage of total extracted fatty acids) were within the ranges of 73.24–74.68% in the skin, 68.36–69.37% in the flesh, 56.20–57.3% in the viscera and 61.21–62.09% in the heads. The greatest amount of the ω-3 fatty acids, especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), were found in fish skin followed by flesh, heads and viscera. The greatest amounts of EPA (9–12%) and DHA (10–14%) were obtained using the soaking and pressure swing techniques. The pressure swing and soaking techniques are the most effective techniques for extracting the ω-3 family of fatty acids from fish samples.